Literature and lustration: Rebuilding social trust through literature. (March 2020) - Morgan, Peter
How do nations, communities and individuals seek to restore individual meaning, social justice and social trust in the wake of traumatic histories? While international legal models have underpinned the processes of lustration in ex-communist countries, other forms of coming to terms with the past have contributed to the rebuilding of social trust in these environments. Literature has taken a role both in preparing the ground for more formal politico-legal processes, and in problematizing single-answer, simplistic or categorical responses to the complex issues of guilt, responsibility, complicity, victimhood and suffering in these societies. The significant new role that European literature has taken since the Holocaust is to come to terms with the past as a record not merely as a history, but as a responsibility and thereby to participate in the processes of lustration and rebuilding of civil society that have formed contemporary Europe.